Colorado water, July/August 2017 - Mokry, Melissa, editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2017)
Newsletter of the Colorado Water Center. Theme: Aquifer storage and recovery.
The newsletter is devoted to highlighting water research and activities at CSU and throughout Colorado.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado